ORKESTRASI BUZZER MELALUI MEDIA SOSIAL MICROBLOGGING DALAM KAMPANYE PENANGANAN VIRUS COVID-19 - Ariandi Putra; Irwansyah Irwansyah (Jurnal Riset Komunikasi (JURKOM), 2020)
In 2020, the world was shocked by the news of the Covid-19 virus. The domino effect in all fields and the taking of many lives is a serious and important issue to anticipate. Microblogging social media is the channel chosen in order to provide an understanding of the community by buzzers. In conducting campaigns on Twitter microblogging, the buzzers involved exchanged messages and information so that the orchestration was carried out simultaneously, in tune, and right on target. In this study, the concepts developed are buzzer, microblogging, and orchestration with qualitative research types and using the literature review method. The results showed that the successful buzzer orchestrated viewed from the distribution of content and information through likes, retweets, and replies from each post. This shows the existence of buzzers in the 4.0 industrial revolution became an important part in every campaign carried out.